Delay in the Effect of Restricting Community Mobility on the Spread of COVID-19 During the First Wave in the United States. (22nd November 2021) - He, Shan; Lee, Jooyoung; Langworthy, Benjamin; Xin, Junyi; James, Peter; Yang, Yang; Wang, Molin
Abstract: Background: It remains unclear how changes in human mobility shaped the transmission dynamic of coronavirus disease 2019 (COVID-19) during its first wave in the United States. Methods: By coupling a Bayesian hierarchical spatiotemporal model with reported case data and Google mobility data at the county level, we found that changes in movement were associated with notable changes in reported COVID-19 incidence rates about 5 to 7 weeks later. Results: Among all movement types, residential stay was the most influential driver of COVID-19 incidence rate, with a 10% increase 7 weeks ago reducing the disease incidence rate by 13% (95% credible interval, 6%–20%). A 10% increase in movement from home to workplaces, retail and recreation stores, public transit, grocery stores, and pharmacies 7 weeks ago was associated with an increase of 5%–8% in the COVID-10 incidence rate. In contrast, parks-related movement showed minimal impact. Conclusions: Policy-makers should anticipate such a delay when planning intervention strategies restricting human movement.